2020
DOI: 10.21203/rs.3.rs-21468/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-administration of vitamin E and atorvastatin improves insulin sensitivity via peroxisome proliferator-activated receptor γ in hyperlipidemic type 2 diabetic patients: a randomized double-blinded clinical trial

Abstract: Background: Contrary to the reports about the useful effects of atorvastatin on blood lipids and insulin sensitivity by up-regulation of peroxisome proliferative-activated receptor gamma (PPAR-γ) expression, to our knowledge, there is inconclusive results about vitamin E. Also, there is no study to assess co-administration of vitamin E and atorvastatin on PPAR-γ mRNA expression, insulin sensitivity and lipid profile in diabetic patients. We compared this effect in hyperlipidemic subjects with type 2 diabetes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In a trial of healthy adults, it was found that a high dose of vitamin E supplementation (300 mg/d) reduced lipid peroxidation [ 107 ], while another study showed that the simultaneous administration of Vitamins E and C resulted in reduced inflammation and enhanced insulin action by promoting non-oxidative glucose metabolism [ 108 ]. In several studies, when vitamin E was co-administered with atorvastatin and vitamin C in people with type 2 diabetes, blood glucose levels decreased [ 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a trial of healthy adults, it was found that a high dose of vitamin E supplementation (300 mg/d) reduced lipid peroxidation [ 107 ], while another study showed that the simultaneous administration of Vitamins E and C resulted in reduced inflammation and enhanced insulin action by promoting non-oxidative glucose metabolism [ 108 ]. In several studies, when vitamin E was co-administered with atorvastatin and vitamin C in people with type 2 diabetes, blood glucose levels decreased [ 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…A stable reference gene is expected to not show inter-subject variation or be affected by the disease condition 21 , 22 . Glyceraldehyde-3-Phosphate Dehydrogenase ( GAPDH ), is extensively used as a reference gene for measuring relative gene expression in PBMCs from diabetics 23 25 . Nevertheless, multiple studies have reported that hyperglycaemia can alter GAPDH expression in cultured cells and animal models 26 28 .…”
Section: Introductionmentioning
confidence: 99%
“…
for measuring relative gene expression in PBMCs from diabetics [23][24][25] . Nevertheless, multiple studies have reported that hyperglycaemia can alter GAPDH expression in cultured cells and animal models [26][27][28] .Meticulous selection of reference genes is of utmost importance for accurate analysis of gene expression data.
…”
mentioning
confidence: 99%
See 1 more Smart Citation